Xerostomia in Sjogren's Syndrome : Presentation of 3 Cases - Arun V Subramaniam; Tulsi Subramaniam; Prashant Jaju (Wolters Kluwer Medknow Publications, 2005)
Sjogren's syndrome first described in 1933, consists of the triad of xerostomia, keratoconjunctivitis sicca, and in half to two thirds of patients, rheumatoid arthritis. The condition has been a subject of controversy pertaining to its diagnosis, etiopathogenesis, management and sequalae. Xerostomia, the oral component of this disorder is a cause of great discomfort. Three cases have been discussed in this article relevant to this condition.